Federalism And Ethnic Conflicts: Ethiopia After 2020 As A Model (Al-Mostansiriyah journal for Arab and international studies, 2025)
Managing ethnic conflicts in modern federal systems is a complex subject that requires a deep understanding of the political and social structures of multiethnic states. Federalism is used as a tool to manage ethnic diversity, but it faces significant challenges in achieving political and social stability. In Africa, federalism has demonstrated limitations in managing ethnic conflicts. Because federal institutional design does not meet the standards required to effectively manage diversity, federalism is often confused with decentralization, leading to unsatisfactory results in managing ethnic conflicts. Federalism, as a tool for managing ethnic conflicts, faces significant challenges in achieving political and social stability in multiethnic states. Experiences in Africa India and Ethiopia demonstrate that federalism alone is not sufficient to resolve ethnic conflicts. It must be supported by strong democratic institutions and a flexible institutional design that adapts to specific circumstances. Ethiopia, under its federal system, has witnessed a marked increase in ethnic conflicts since 2020. This system, established after the fall of the military regime in 1991, aims to grant autonomy to various ethnic groups. However, this structure has exacerbated conflicts between these groups.Keywords research : Federal system, ethnic conflicts, self-rule.